Implications of Learning in Islamic Religious Education in Forming Students' Attitudes of Religious Tolerance - Ainin Najah; Imam Syafe'i; Amiruddin Amiruddin (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze the implementation of Islamic religious education learning in shaping students' religious tolerance. The research focuses on three things: strategy, forms of religious tolerance, and their implications. This research was conducted at SMAN 1 Seputih Mataram. This study uses a qualitative research approach that describes the data sources obtained from the field. Data collection is carried out using observation, interviews, and documentation. The data is then analyzed by managing data from sources, explaining, and drawing conclusions. The results of the study revealed that the efforts made by Islamic religious education teachers in forming an attitude of tolerance between religious communities were: 1) motivating the characters' stories. 2) Carry out attitude habituation exercises according to multicultural values. 3) carrying out Islamic Religious Education learning by guiding by carrying out the values ​​of discipline, honesty, mutual respect, and respect and helping each other. The motivation and habituation of multicultural education are carried out by encouraging them to participate in extracurricular activities, respecting each other, and inspiration through stories.